1956
DOI: 10.1002/aic.690020405
|View full text |Cite
|
Sign up to set email alerts
|

Rate of rise or fall of liquid drops

Abstract: Measurements of the terminal velocity of liquid drops immersed in an insoluble liquid were made for eleven liquid systems, covering a wide range of physical properties: continuous-phase density 0.960 to 1.145 g./cc., viscosity 0.93 to 1.56 centipoises; dispersed-phase density 0.807 to 1.674 g./cc., viscosity 0.59 to 72.1 centipoises; interfacial tension 0.3 to 42.4 dynes/cm. A correlation of the data was developed for each of the two velocity-dropdiameter regions which permits easy computation of the drop velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(84 citation statements)
references
References 5 publications
6
77
0
1
Order By: Relevance
“…Correlations by Klee and Treybal (1956), Hu and Kintner (1955), Johnson and Braida (1957), Edge and Grant (1971), and Grace et al (1976) were discussed by Skelland et al (1987) and are shown in Appendix B. These correlations were developed for a liquid droplet moving at terminal velocity through another liquid phase, and they may not be easily extrapolated to the case of liquid droplets in a gas.…”
Section: Flow Transitionsmentioning
confidence: 99%
“…Correlations by Klee and Treybal (1956), Hu and Kintner (1955), Johnson and Braida (1957), Edge and Grant (1971), and Grace et al (1976) were discussed by Skelland et al (1987) and are shown in Appendix B. These correlations were developed for a liquid droplet moving at terminal velocity through another liquid phase, and they may not be easily extrapolated to the case of liquid droplets in a gas.…”
Section: Flow Transitionsmentioning
confidence: 99%
“…Comparison of calculated results with criterion values, showed that most drops were under the oscillation condition. Klee and Treybal (1956) proposed an expression for the critical diameter cr , d Figure 2. Note that the diameters of droplets ranged from 1.66 to 3.49 mm and were larger than the calculated d cr .…”
Section: Hydrodynamic Investigationmentioning
confidence: 99%
“…A number of authors describe the suitability of velocity correlations for specific droplet size ranges or certain physical properties [26,[37][38][39][40]. A selection of these velocity correlations has been implemented in simulation program.…”
Section: Droplet Velocitymentioning
confidence: 99%